A Manufacture of Phosphate Fertilizer from Cow Bones Waste: Phosphate Fertilizer - N W Sari; F A Putri; D S Perwitasari (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
Cow bone waste was the fundamental problems that occur in several abattoirs (slaughterhouses) in Indonesia that untapped optimally. Intention of this research studied of making phosphate fertilizer from cow bone wasted by granulation process with the effect of concentration phosphoric acid and sulfuric acid to the quality of phosphate fertilizer. The process of making phosphate fertilizer was by preparation of cow bone waste until became into powder and filtered it with 80 mesh of sieve. Pan granulator ran with cow bone powder and sprayed with sulfuric acid-phosphoric acid solution according to specified variable. Then the results of granulation taken from a pan granulator and dried using an oven with a temperature of 70oC for 3 hours. The chemical composition of dried products were analyzed using XRF (X-Ray Fluorescence) analysis. Analysis results showed that phosphate fertilizer can be produced by cow bone waste deliver the highest P2O5 was 30.7% with addition H2SO4 5% and H3PO4 45%.